A párhuzamosok és a végtelen : Montenegró kiválása az aszimmetrikus államszövetségből és az önállóság persektívái - Pap, Tibor (Közép-Európai Közlemények, 2011)
The dissolution of Yugoslavia was a tragic process that also projected additional medium-term questions. Regarding the member states of Yugoslavia becoming autonomous, Montenegro was the last in this series. Complex social and political processes influenced the discourse on separation/confederation from both the Serbian and the Montenegro sides. The final event of separation did not really surprise anyone, but neither was it inevitable (its socio-and politico-theoretical requirements are also covered in the text). The process of secession –ethnically-based spatial delimitation –have not stopped, however. Due to the fractal nature of this series, the smallest former Yugoslavian republic also faces serious challenges: this is the only new state which does not have an absolute majority. Additionally, linguistic rifts (faults) complicate the distinctions of ethnic identity. The present study attempts to point out the present and medium-term issues involved.